1999
DOI: 10.3109/10428199909145726
|View full text |Cite
|
Sign up to set email alerts
|

CD148, a New Membrane Tyrosine Phosphatase Involved in Leukocyte Function

Abstract: Protein tyrosine phosphatases play an essential role in the control of leucocyte cell growth an differentiation. Recently a new receptor type membrane tyrosine phosphatase named CD148 has been identified. This molecule is present on the membrane of all the hematopoietic lineages as well as on several other cell types, mainly epithelial cells and its expression increases after cell activation. This molecule is able to act as a transducing molecule. Moreover, CD148 is able to modulate the signal transduction thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 24 publications
(7 reference statements)
1
18
0
Order By: Relevance
“…CD148, also known as Ptprj or DEP-1, is a receptor-like protein tyrosine phos phatase (RPTP) that is comprised of an extracellular domain consisting of 8 fibronectin-type repeats, a transmembrane domain, and a cytoplasmic phosphatase domain. CD148 is highly expressed on both hematopoietic and nonhematopoietic cells, including cells of the lung (11)(12)(13). The physiologic function of CD148 outside of the hematopoietic system remains obscure, although it has been shown to be upregulated in epithelial cells grown at high density and has been implicated in regulating contact inhibition of cell growth.…”
Section: Introductionmentioning
confidence: 99%
“…CD148, also known as Ptprj or DEP-1, is a receptor-like protein tyrosine phos phatase (RPTP) that is comprised of an extracellular domain consisting of 8 fibronectin-type repeats, a transmembrane domain, and a cytoplasmic phosphatase domain. CD148 is highly expressed on both hematopoietic and nonhematopoietic cells, including cells of the lung (11)(12)(13). The physiologic function of CD148 outside of the hematopoietic system remains obscure, although it has been shown to be upregulated in epithelial cells grown at high density and has been implicated in regulating contact inhibition of cell growth.…”
Section: Introductionmentioning
confidence: 99%
“…A few studies examining the expression of CD148 in human lymphocytes, especially T cells, have been published (1,10). These studies showed that CD148 is expressed at low levels on resting T cells, but is upregulated following activation (1,10).…”
mentioning
confidence: 99%
“…Less is known about CD148 expression on thymocytes. Immunohistochemical staining of human thymi revealed that CD148-positive T cells are localized in medulla, suggesting its expression in mature thymocytes (5,9). This was supported by flow cytometry that detected CD148 only on CD3-positive thymocytes (5).…”
mentioning
confidence: 54%
“…Moreover, murine thymocytes were almost CD148-negative with a weak signal only at early stages (10). In contrast, the limited data available on human thymi suggested that the regulation of CD148 expression on human thymocytes may be very different, with CD148 expression appearing at the later stages of T cell development (5,9). However, no detailed subset analysis has been carried out.…”
Section: Cd148 Is Differentially Expressed On Human and Murine Tmentioning
confidence: 95%